2015
DOI: 10.3168/jds.2014-8380
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of factors influencing the result of a Mycobacterium avium ssp. paratuberculosis antibody ELISA in milk of dairy cows

Abstract: The influence of milk yield and milk composition on the diagnosis of Mycobacterium avium ssp. paratuberculosis (MAP) by milk ELISA in the context of the total IgG secretion patterns in milk throughout lactation and serum concentrations were investigated. A 2-yr trial was performed in which 1,410 dairy cows were sampled monthly and MAP milk ELISA status and milk yield and composition were determined. Data were analyzed by mixed model analysis. Milk yield was found to significantly influence ELISA results expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 31 publications
3
24
0
3
Order By: Relevance
“…Given that cows in the seasonal-and split-calving study herds calved over several weeks, it is not surprising that the model-based mean BTM ELISA ODC% was significantly higher at 5 to 8 wk compared with ≥13 wk after the commencement of the calving period in these herds ( Figure 2). The subsequent decline in the model-based mean BTM ELISA ODC% from 5 to 8 wk onward is also consistent with studies that have demonstrated that total individual milk IgG concentrations decrease as the number of days in lactation increase (Liu et al, 2009;Eisenberg et al, 2015). Therefore, the relationship between time after the commencement of the calving period and BTM ELISA ODC% may be attributable not just to the temporal relationship to calving but also to individual cow milk production factors.…”
Section: Discussionsupporting
confidence: 86%
“…Given that cows in the seasonal-and split-calving study herds calved over several weeks, it is not surprising that the model-based mean BTM ELISA ODC% was significantly higher at 5 to 8 wk compared with ≥13 wk after the commencement of the calving period in these herds ( Figure 2). The subsequent decline in the model-based mean BTM ELISA ODC% from 5 to 8 wk onward is also consistent with studies that have demonstrated that total individual milk IgG concentrations decrease as the number of days in lactation increase (Liu et al, 2009;Eisenberg et al, 2015). Therefore, the relationship between time after the commencement of the calving period and BTM ELISA ODC% may be attributable not just to the temporal relationship to calving but also to individual cow milk production factors.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies investigating factors that influence the outcome of MAP ELISA in milk have suggested the role of a number of factors including milk yield (concentration of MAP-specific antibodies, mainly related to days in milk, DIM), herd (prevalence of JD), and parity (related to number of lactation) were mainly attributed [ 30 , 31 ]. In our investigation, days in milk (DIM) and lactation numbers were considered for animals in each group, and the results show no significant difference for DIM and lactation number between groups ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…During early stages of infection, a cellular immune response is produced, whereas antibody production develops in later stages of infection, which translates to different test accuracy in different stages of infection (Stabel et al, 2014;Laurin et al, 2015Laurin et al, , 2017. Although serum ELISA specificity is considered to be greater than 97%, sensitivity can vary from 15 to 75% depending on the stage of the disease (Timms et al, 2011;Mitchell et al, 2015) and also on milk yield, lactation, herd prevalence, DIM, milk protein, and SCC (Eisenberg et al, 2015).…”
Section: Introductionmentioning
confidence: 99%